2017
DOI: 10.17221/55/2016-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of DNA methylation in diploid and tetraploid apple (Malus × domestica Borkh.)

Abstract: He P., Cheng L., Li H., Wang H., Li L. (2017): A comparative analysis of DNA methylation in diploid and tetraploid apple (Malus × domestica Borkh.). Czech J. Genet. Plant Breed., 53: 63−68.DNA methylation is one of the major epigenetic modifications. It is very important to the regulation of gene expression. Methylation-sensitive amplification polymorphism (MSAP) profiling was applied to a diploid apple cultivar and its derived autotetraploid in order to characterize the level and pattern of DNA methylation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…We suspect that the process of entering dormancy and then resuming growth following low temperature treatment may be one of the factors involved in genome stabilization related to decreased DNA methylation. In contrast, He et al [ 46 ] reported that DNA methylation rates, based on MSAP analysis, were very similar between diploid and tetraploid plants of ‘Hanfu’ apple, implying that chromosome doubling had no effect on the global level of DNA methylation. It was also confirmed by transcriptome analysis, which revealed that polyploidization had no discernible effect on the expression level of any of the DNA methylation-related genes, MET1 , DRM2 , and CTM3 .…”
Section: Discussionmentioning
confidence: 98%
“…We suspect that the process of entering dormancy and then resuming growth following low temperature treatment may be one of the factors involved in genome stabilization related to decreased DNA methylation. In contrast, He et al [ 46 ] reported that DNA methylation rates, based on MSAP analysis, were very similar between diploid and tetraploid plants of ‘Hanfu’ apple, implying that chromosome doubling had no effect on the global level of DNA methylation. It was also confirmed by transcriptome analysis, which revealed that polyploidization had no discernible effect on the expression level of any of the DNA methylation-related genes, MET1 , DRM2 , and CTM3 .…”
Section: Discussionmentioning
confidence: 98%
“…Comparing the level of expression of three genes modulated DNA methyltransferase exposed the lowest expression was MET1 the plant, while in the leaf, flower and fruit expression of DRM2 was expressed more, and CTM3 was high expression in the fruit. The transcription level of the three transcripts was no discernible effect on ploidy [115]. It has changed in the genome of diploid and its autopolyploid Phlox drummondii Hooker when comparing the difference of generations of autopolyploid (C 0 , C 1 , C 2 , and C 3 ).…”
Section: Iicpk2 Expressionmentioning
confidence: 94%
“…Methylation, the effect of ploidy in some gene expression Similar between the two ploidy levels (28.0% vs 27.3%) with the frequency of methylated restriction sites, no discernible effect on ploidy in the expression of MET1, DRM2, CTM [115] Phlox drummondii…”
Section: Diploid and Autotetraploidmentioning
confidence: 96%
“…Alteration on gene expression in polysomic polyploid was not high such as Paspalum notatum in 10,000 genes showed 42 homologous genes to 26 divergent genes having function and 22 novel sequences [16], 4.3% divergent expression in Isatis indigotica [17], 10% genes changed expression in potato [18], 6.09% pivotal differential expression in P. fortunei [19], 2.87% changed level of gene expression in Mulberry (Morus alba L.) [20], 11.5% of transcriptome and proteome correlation between diploid and tetraploid P. tomentosa [21], 17% differential gene expression in Tolmiea (Saxifragaceae) [22], 2677 unigenes were significantly divergently expressed in tetraploid P. tomentosa [23], 22 genes that happened alternative splicing, showing abilities of making the difference of isoforms of protein in watermelon [24]. Methylation occurred in polysomic polyploid in rice, Malus × domestica Borkh, B. rapa [13] [25] [26].…”
Section: Introductionmentioning
confidence: 99%